(untitled) (aSSIST Business Review, 2026)
Background/Purpose Advances in medical technology, population ageing, and increased life expectancy are reshaping social needs for continuous education. University lifelong education centres play a critical role in enabling early retirees and the silver generation to prepare for second careers and improved quality of life. Effective marketing message strategies are essential to communicate the value of these educational programmes. This study investigates how message framing and consumers’ regulatory focus orientation jointly shape consumer attitudes and behavioural intentions toward lifelong education courses. Study Design/Methodology/Approach A 2 (message framing: positive vs. negative) × 2 (regulatory focus: promotion focus vs. prevention focus) experimental design was employed. Marketing messages for a university lifelong education centre were designed virtually: a positive framing condition (’If you take the lifelong education course, you can maximise your job competitiveness’) and a negative framing condition (’If you do not take the lifelong education course, you may miss job opportunities’). Survey data were collected and analysed using analysis of variance (ANOVA) and bootstrap procedure to verify interaction effects between message framing and regulatory focus tendency. Findings Promotion-focused consumers demonstrated more positive brand attitudes and higher purchase intentions under positive framing, consistent with their orientation toward achievement and benefit maximisation. Prevention-focused consumers formed higher brand trust and purchase intentions under negative framing, reflecting their emphasis on risk avoidance and stability. These interaction effects confirm that customised message design based on consumers’ psychological orientation effectively induces behavioural response. Specifically, providing gain-framed messages (’You can learn new skills through lifelong education and successfully prepare for old age’) to promotion-focused audiences, and loss-framed warning messages (’If you do not receive lifelong education, you may lose the opportunity to prepare for old age’) to prevention-focused audiences, are demonstrably more effective than uniform messaging. Originality/Value This study is the first to comprehensively apply message framing and regulatory focus theories to the specific marketing context of university lifelong education centres in an ageing society. It provides practical implications for education marketing practitioners seeking to tailor messages to the psychological characteristics of early retirees and older learners, and contributes to the broader literature on framing effects in educational service marketing.